A comparative study on the cleaning efficacy of a pulsed vacuum cleaning and disinfection device on rigid endoscopic instruments in a hospital setting - Bo, Licong; Wang, Xue; Li, Jian; Hu, Yue (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveGiven the increasing demand for rapid and reliable instrument reprocessing to support surgical schedules and minimize infection risks, this study aims to explore the cleaning efficacy of a pulsed vacuum cleaning and disinfection device on rigid endoscopic instruments in a comparative hospital setting.MethodsA total of 800 rigid endoscopic instruments scheduled for post-operative cleaning in our hospital’s sterilization supply room between July and December 2024 were included in the study. After pre-treatment, the instruments were divided into two groups, with 400 instruments in each group. The control group used a vacuum ultrasonic cleaner, while the observation group used a pulsed vacuum cleaning and disinfection device. The cleaning time, cleaning effect, protein residue detection, and instrument damage rate were compared between the two groups. A cost-effectiveness analysis was also performed.ResultsThe cleaning time in the observation group was significantly shorter than that in the control group, with a statistically significant difference (P<0.05). There was no statistically significant difference between the two groups in terms of visual inspection, magnifying light source, and ATP fluorescence comparison (P>0.05). The protein residue detection in the observation group was lower than that in the control group, with a statistically significant difference (P<0.05). The instrument damage rate in the observation group was lower than that in the control group, with a statistically significant difference (P<0.05). The pulsed vacuum device demonstrated significant cost savings, with a lower total cost ($15,984 vs. $21,832) and cost per qualified instrument ($40.26 vs. $55.98) over 400 cycles.ConclusionThe pulsed vacuum cleaning and disinfection device can effectively clean rigid endoscopic instruments and is worthy of clinical promotion as it enhances operational efficiency and upholds high standards of patient safety by ensuring instrument cleanliness.